Serum antibody-negative Goodpasture syndrome with delta granule pool storage deficiency and eosinophilia - Kussman, Ashleigh (Clin Kidney J, 2012)
Goodpasture syndrome is a rare, life-threatening autoimmune disease characterized by a triad of rapidly progressive glomerulonephritis, a hemorrhagic pulmonary condition and the presence of anti-glomerular basement membrane (anti-GBM) antibodies. The antibodies initiate destruction of the kidney glomeruli, resulting in a focal necrotizing glomerulitis, which may progress rapidly to renal failure. Autoantibody-mediated damage of alveolar basement membranes leads to diffuse pulmonary hemorrhage, which in some cases may be severe enough to cause respiratory failure. Many clinicians use a variety of assays to detect serum anti-GBM antibodies; however, these tests may be falsely negative in up to 15% of patients with Goodpasture syndrome. Here, we report an unusual case of a 40-year-old man with clinical evidence of Goodpasture syndrome, a negative anti-GBM antibody serum result, eosinophilia and delta granule pool storage deficiency. After a 14-day hospital stay and extensive workup, as well as treatment with antibiotics, steroids and ventilator support for respiratory failure, the patient continued to deteriorate and entered multisystem organ failure. The family decided to withdraw ventilator support, and the patient expired. Immunofluorescence testing for anti-GBM autoantibodies on lung and kidney tissues during an autopsy confirmed the diagnosis of Goodpasture syndrome.